(untitled) (Medical Forum Monthly, 2024)
Background: In the recent years the fire arm possession and its use in violence has superseded many times the conventional means used even in rural setup. This study was conducted to know the pattern of injuries in fire arm related deaths, the prevalence of firearm weapons used in violence and the time interval the victim survived after sustaining injures in such incidences. Study Design: Observational Study. Place and Duration of Study: This study was conducted at DHQ, Hospital kasur during the period from 1st January 2008 to 31st December 2010. Materials and Methods: This study includes 199 cases where death was due to some fire arm weapon out of total 451 cases autopsied at District Head Quarters Hospital kasur. Results: The rate of fire arm related deaths during this period was 44.12%. Males accounted for 80.90% and females were 19.10%. In 60.30% cases death took place immediately after sustaining injuries, in 26.63% it was within minutes and in3.51% the victim survived for hours after being injured. In9.51% cases the victim remained admitted in hospital and died there due to some injury related complications. Conclusion: An interdisciplinary approach is required to control fire arm weapons possession, to educate the masses especially youngsters about sanctity of human life and how to control the nerves during periods of mental irritability and instability.